A Treat-to-Target Strategy Preserves Work Capacity in a Rheumatoid Arthritis Inception Cohort Treated With Combination Conventional DMARD Therapy. Issue 3 (April 2017) - Wechalekar, Mihir D.; Quinn, Stephen; Lester, Susan; Metcalf, Robert G.; Shanahan, Ella; Walker, Jennifer G.; Smith, Malcolm D.; Hill, Catherine L.; Shanahan, E. Michael; Proudman, Susanna M.
Abstract : Objectives: Quantification of work disability in patients with early rheumatoid arthritis (RA) receiving conventional DMARDs according to a treat-to-target strategy. Methods: This is a retrospective cohort analysis of RA patients who received combination conventional DMARDs, escalated to achieve DAS28(ESR) remission and completed an annual work and arthritis questionnaire. Random effect mixed modeling was used to assess associations between average hours worked per week (HWPW), and baseline prognostic factors. HWPW were compared with matched population averages. Cox proportional hazards modeling was employed to evaluate associations between permanent loss of employment and treatment response, disease and demographic factors. Results: Work data from 135 patients working at baseline and 137 working at any point followed for up to 14 years (range 1–14) were available for analysis. The mean age was 45 years, 70% were female, and 70% and 68% were seropositive for rheumatoid factor and anti-cyclic citrullinated peptide (anti-CCP), respectively. Men worked more hours than women; there was a highly significant association between working hours lost and increasing age (0.28 hours, P = 0.04) and female gender (11.92 hours, P < 0.001). HWPW were maintained over the study time comparable to the general population (loss of 0.78 vs. 0.24 HWPW). EULAR good responders at 6 months were more likely to be working at 10 years compared to those with moderate/no response. Permanent loss of employment and baseline age were strongly associated for anti-CCP positive participants ( P = 0.04). Conclusions: Treat-to-target combination conventional DMARD therapy maintains work capacity, particularly in good responders, comparable to the general population. Improving treatment response in moderate/no responders early in disease may increase work retention.